Low-Phosphate Chromatin Dynamics Predict a Cell Wall Remodeling Network in Rice Shoots . Issue 3 (19th December 2019) - Foroozani, Maryam; Zahraeifard, Sara; Oh, Dong-Ha; Wang, Guannan; Dassanayake, Maheshi; Smith, Aaron P.
Abstract : Combined chromatin structural data reveals specific chromatin-state transitions that correlate with subsets of functionally distinct rice genes differentially expressed under phosphate starvation. Abstract: Phosphorus (P) is an essential plant macronutrient vital to fundamental metabolic processes. Plant-available P is low in most soils, making it a frequent limiter of growth. Declining P reserves for fertilizer production exacerbates this agricultural challenge. Plants modulate complex responses to fluctuating P levels via global transcriptional regulatory networks. Although chromatin structure plays a substantial role in controlling gene expression, the chromatin dynamics involved in regulating P homeostasis have not been determined. Here we define distinct chromatin states across the rice ( Oryza sativa ) genome by integrating multiple chromatin marks, including the H2A.Z histone variant, H3K4me3 modification, and nucleosome positioning. In response to P starvation, 40% of all protein-coding genes exhibit a transition from one chromatin state to another at their transcription start site. Several of these transitions are enriched in subsets of genes differentially expressed under P deficiency. The most prominent subset supports the presence of a coordinated signaling network that targets cell wall structure and is regulated in part via a decrease of H3K4me3 at transcription start sites. The P starvation-induced chromatin dynamics and correlated genes identified here will aid in enhancing P use efficiency in crop plants, benefitting global agriculture.